An Analog Array Approach to Variable Topology Filters for Multi-mode Receivers - Csipkes, D.; Csipkes, G.; Hintea, S.; Fernandez-Canque, H. (Elektronika ir Elektrotechnika, 2010)
This paper presents some system level investigations on the possibilities to implement reconfigurable topology filters intended for wireless applications. The proposed filter is built around a signal bus and a current mode configurable analog block that support the mapping of various filter orders and synthesis methods onto the same circuit. The selectivity of the filter can be extended to arbitrary transmission zeros and complex band pass type of responses. The different configurations have been tested through Eldo simulations, including first order non-idealities of the building blocks.